#### Answer

$f'(x)=25x^4+39x^2-6$

#### Work Step by Step

$f(x)=(5x^2-2)(x^3+3x)$
Use the product rule.
$f'(x)=(5x^2-2)(3x^2+3)+(x^3+3x)(10x)$
Distribute.
$f'(x)=15x^4+15x^2-6x^2-6+10x^4+30x^2$
Combine like terms.
$f'(x)=25x^4+39x^2-6$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$f'(x)=25x^4+39x^2-6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.